Testing Convenience Theory for White-collar Crime: Perceptions of Potential Offenders and Non-offenders. Issue 7 (3rd July 2022) - Stadler, William A.; Gottschalk, Petter
ABSTRACT: Convenience theory is a novel, integrated theory aimed at explaining criminal behavior, with a particular focus on white-collar crime. The current study represents a preliminary test of this theory through a survey of student perceptions of financial crimes committed by business leaders and executives. Four dimensions of the theory, including justifications, motivations, opportunities, and willingness to commit crime, are examined using an international sample of students from two different universities. Results reveal significant differences between students' agreement with justifications for white-collar crime. Those more likely to agree with crime justifications were also more likely to agree with motivations for and willingness to engage in executive leader crimes associated with a business. Thus, the current study finds support for convenience theory as a possible explanation for white-collar criminality among those expected to be in future positions which make these crimes possible. Findings also implicate motivation and willingness, two important dimensions in convenience theory, as key factors which are likely to influence the decision-making process to engage in white-collar crime.